Employee Performance Based on Transactional Leadership Style, Employee Competence and Job Satisfaction - Yohana F. Cahya Palupi Meilani; Margaretha Pink Berlianto; Leonardo M. Canoy, Jr; Elvitriana Intan Novita; William Marvincent Tan (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2025)
This study aims to examine the impact of transactional leadership style, employee competence, job satisfaction, and employee performance. The research follows a quantitative approach, utilizing a questionnaire with Likert scale responses from 1 to 5. Conducted at PT XYZ, the study employs purposive sampling, meaning respondents must meet specific criteria to have their responses accepted. The total sample consists of 100 participants. Data analysis was performed using the SmartPLS 4 software with the PLS-SEM (Partial Least Squares – Structural Equation Modeling) method. The findings reveal that transactional leadership style positively and significantly influences job satisfaction, employee competence has a positive and significant effect on job satisfaction, transactional leadership style positively and significantly affects employee performance, and employee competence also positively and significantly impacts employee performance. However, job satisfaction has a negative and significant effect on employee performance. It is hoped that readers will apply the positive insights from this research to enhance the company’s sustainability.